Video Treatment Re-Examined: Enactments, Erotic Transference, and the Third: Reply to Lyons and Williams. Issue 3 (3rd May 2020) - Ringel, Shoshana
Abstract : This discussion will address clinical, procedural, and theoretical issues raised by Lyons and Williams in response to my paper. I will elaborate on potential enactments, the erotic transference, and the third as related to the case.